Analisis kelayakan isi buku siswa kelas v tema ekosistem di sekolah dasar - Sekar Mustika Saraswati; Jenny Indrastoeti Siti Poerwanti; Sularmi Sularmi Sularmi (Universitas Sebelas Maret, 2021)
This study aims to describe the acceptability of the contents of the Grade V Student Book by the Ecosystem Theme. This research used descriptive qualitative research methods. The research approach is contents analysis. As a data collection technique, the writer used documentation technique. As data analysis, the writer used descriptive qualitative technique. As a data validity technique, the writer used investigator triangulation technique. In this study, there are four dimensions were analyzed which are the spiritual dimension, the dimension of social attitudes, the dimension of knowledge, and the dimension of skills. The results showed that the grade V Student Book by the Ecosystem Theme is included in the very acceptable category with the percentage of the acceptability score in the spiritual dimension is 65.28%, the acceptability of the social attitude dimension is 100%, the acceptability of the knowledge dimension is 93.52%, and the acceptability of the the skill dimension is 86.11%. This study has theoretical implications, namely that book can support the implementation of curriculum learning 2013 in schools. The study also has pratical implications, this study can be used as a reference material for teachers and schools to choosing books that suit the needs of students.